Algebraic Cubic Equation vs. Freedman Equations for the Geometry of our Universe - Kalimuthu, S (Annals of Mathematics and Physics, 2024)
In 1921 the famous Russian mathematician Alexander Freedman proved by analyzing Einstein’s general relativity that the geometry of our Universe has three possibilities namely Euclidean, Hyperbolic, and Spherical. Various cosmological experimental and observational probes of BOOMERanG, NASA’s WMAP, and ESA’s PLANCK mission revealed that the shape of our universe is flat. But to this day, there is no mathematical formulation for the geometry of our universe. In this short work, the author attempts to show that the geometry of our universe is Euclidean.